Incomplete ascent of left kidney with non rotation-a rare congenital anomaly - Varsha Prabhakar Dahiphale; Mangesh Santram Selukar; Geetanjali Bhagawanrao Sudke; Promod Raghunath Kulkarni (Wolters Kluwer Medknow Publications, 2016)
Anomalies of the urinary system form a significant portion of the congenital malformation as a whole. Anomalies of kidney have been frequently reported. Anomalies may occur in number, position, shape, size and rotation of kidney. Structural, positional and vascular anomalies are the most frequently reported. Rotational anomalies form a rare entity not cited in most of the embryology text books. Now a days knowledge of variations in kidney position, rotation and variations in renal vessels are becoming more important due to gradual increase in interventional radiological procedures, urological and vascular operations and renal transplantation. In this paper a rare case of incomplete ascent and non rotation of left kidney is reported during routine dissection of 55 year old male cadaver. An attempt has been made to systematically document these variations and give possible explanation for the same. The detailed knowledge of these morphological variations will be useful for many urological and radiological procedures.